Marsidudu, a model of maintaining the ethnicity identity beyond traditional practice of warming up postpartum mothers - Rizky Fadillah Lubis; Fotarisman Zaluchu; Sabariah Bangun; Irfan Simatupang (Cogent Arts & Humanities)
Warming up the body of a postpartum mother is a common tradition in Asian countries, including Indonesia. This local tradition, marsidudu, turns out to be very much connected with the maintenance of the ethnic identity by the members, including when they no longer have the domicile in their original area. In a new place, the spirit to maintain the identity is conducted through the medium of a postpartum mother’s body and with the support of different power relation between a mother-in-law and her daughter-in-law in conducting the marsidudu practice. This unique ritual keeps an interesting narration, not only about the traditional practice but also about the insight on how an ethnic keeps maintaining itself.